Foraging behavior of wood mice as related to presence and activity of genets (JOURNAL OF MAMMALOGY, 2005)
Predators influence the distribution of prey directly if predation reduces local population density, or indirectly if the presence of predators induces behavioral or physiological responses to predation risk. We analyzed whether the foraging behavior of wood mice (Apodemus sylvaticus) was affected by the presence and activity of small-spotted genets (Genetta genetta) at ``risky{''} baiting stations monitored with automatic cameras. Sampling stations in 6 x 6 grids spaced at 250 m were arranged in 3 habitat types (shrubland, pine woodland, and holm oak woodland). Grids were sampled systematically by means of groups of 2-9 cameras monitoring sampling stations during a week. We obtained 377 independent contacts of wood mice and 35 independent contacts of at least 8 different genets. Patterns of habitat use by genets and wood mice were spatially discordant, because only 2 cameras detected both. Wood mice visited baits more often and during longer periods in groups of sampling stations where genets were not detected than in groups where genets were detected within the same week. Mean time spent foraging by genets negatively influenced both the number of foraging bouts per night and the mean duration of such bouts by mice using nearby baits. Finally, temporal patterns of activity of mice along the night were different depending on whether genets were foraging nearby. Temporal patterns of mice when and where genets were absent were positively correlated with patterns of genet activity, whereas mice patterns were negatively correlated with genet patterns when and where genets were present. Sampling dates, habitat types, and moonlight levels did not seem to have influenced these results. Wood mice showed spatial and temporal changes in foraging behavior in response to the presence of genets, and decisions about how often and how long to forage were affected by foraging activity of genets. Results obtained provided direct evidence of a foraging game of stealth and fear between mice and their predator that could help to explain mice distribution in Mediterranean postfire habitats.